2023
DOI: 10.1039/d3ta01415k
|View full text |Cite
|
Sign up to set email alerts
|

Highly reversible, dendrite-free and low-polarization Zn metal anodes enabled by a thin SnO2layer for aqueous Zn-ion batteries

Abstract: Aqueous Zn-ion batteries (AZIBs) are attractive for next-generation renewable and secure energy storage systems due to their high safety and low cost. However, dendrite growth and side reactions of Zn...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…So far, much effort has been put to improve the electrochemical reversibility of Zn anodes by means of constructing 3D conductive hosts, electrolyte additives, or surface coatings. Nevertheless, organic additives in the aqueous electrolyte may reduce ionic conductivity . For the coating technology, normally, the first step was the ex situ preparation of coating materials, which was then applied onto the Zn foil surface through a slurry-coating process.…”
Section: Introductionmentioning
confidence: 99%
“…So far, much effort has been put to improve the electrochemical reversibility of Zn anodes by means of constructing 3D conductive hosts, electrolyte additives, or surface coatings. Nevertheless, organic additives in the aqueous electrolyte may reduce ionic conductivity . For the coating technology, normally, the first step was the ex situ preparation of coating materials, which was then applied onto the Zn foil surface through a slurry-coating process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Tw80, as a nonionic surfactant, can help to improve the surface wettability between Zn electrode and electrolyte, which may assist in the uniform distribution of Zn 2+ ions. Meanwhile, the MoO 2 coating layer plays a more pronounced role in significantly reducing the contact angle to almost 0° in the solutions with and without Tw80 (Figure S18c,d), making the coated Zn surface superhydrophilic in the electrolyte possibly by enhancing the surface roughness or heterogeneity. , It has been reported that the electrode wettability plays a role in the final Zn deposition pattern and high surface hydrophilicity will result in more uniform Zn 2+ flux across the surface of MoO 2 @Zn anodes, contributing to homogeneous Zn nucleation and growth . Consequently, the MoO 2 coating provides improved electrolyte–anode interfaces and hence enhances Zn 2+ transport kinetics.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, MoO 2 coating can significantly enhance surface hydrophilicity to improve the wetting of electrolyte on the Zn electrode, which is beneficial for reducing the desolvation energy of hydrated Zn ions . To determine the activation energy of Zn 2+ desolvation under the protection of diverse MoO 2 coatings, EIS measurements of diverse MoO 2 @Zn symmetric cells in ZnSO 4 +1Tw80 electrolyte were conducted at the temperature range from 30 to 60 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The ratio of (003) peak intensity to (104) peak intensity is widely employed to estimate Li + /Ni 2+ mixing in layered structures. 46 A higher I 003 / I 104 value indicates lower cation mixing. An I 003 / I 104 value exceeding 1.2 generally indicates an acceptable Li/Ni mixing rate.…”
Section: Resultsmentioning
confidence: 99%